A prospective, randomised, controlled, double blinded, cross-over study on the effect of a single session of pulsed electromagnetic field therapy on signs of hip osteoarthritis in dogs - Leung, Gillian; Junnila, Jouni; Björkenheim, Thomas; Tiainen, Helena; Hyytiäinen, Heli Katariina (Acta veterinaria scandinavica, 2024)
Background Canine coxofemoral joint osteoarthritis is a common, painful and debilitating condition. The objective of this study was to evaluate if any measurable changes in pain or lameness occurred in this patient group immediately after a single treatment with pulsed electromagnetic field therapy. Eight dogs with coxofemoral joint osteoarthritis presenting with signs of pain and lameness were prospectively recruited to this randomised, controlled, double blinded, cross-over study. Subjects attended the research facility on two occasions for one active and one placebo treatment with pulsed electromagnetic field therapy. The immediate effect of one pulsed electromagnetic field therapy treatment on pain and lameness was measured subjectively with the Helsinki Chronic Pain Index and Visual Analogue Scale and objectively using a pressure sensitive walkway. Results A statistically significant difference ( P = 0.03) for change in stride length in the affected limb was recorded for subjects between the active and placebo treatments with pulsed electromagnetic field therapy. Within the active treatment results, there was a statistically significant change in the measurement for reach ( P = 0.04) and stride length ( P = 0.047) which got shorter in the affected limb post treatment. For the subjective outcome measures, there was no statistically significant difference between the active and placebo treatments for the evening of the treatment day or the next morning from pre-treatment values. Within the placebo treatment results a statistically significant change (improvement) was detected in Visual Analogue Score ( P = 0.03) between pre-treatment and the next morning values. Conclusions The findings of this study do not show demonstrable improvement in owner assessed pain levels or temporospatial performance in dogs with coxofemoral joint osteoarthritis immediately after a single application of pulsed electromagnetic field therapy.